Application of advanced brain positron emission tomography–based molecular imaging for a biological framework in neurodegenerative proteinopathies. Issue 1 (16th April 2019) - Perani, Daniela; Iaccarino, Leonardo; Jacobs, Andreas H.; ,; Lammertsma, Adriaan A.; Nordberg, Agneta; Windhorst, Albert D.; Gerhard, Alexander; Winkeler, Alexandra; Jacobs, Andreas H.; Gee, Anthony; Kuhnast, Bertrand; et al.
Abstract: Introduction: A rapid transition from a clinical‐based classification to a pathology‐based classification of neurodegenerative conditions, largely promoted by the increasing availability of imaging biomarkers, is emerging. The Framework for Innovative Multi‐tracer molecular Brain Imaging, funded by the EU Joint Program ‐ Neurodegenerative Disease Research 2016 "Working Groups for Harmonisation and Alignment in Brain Imaging Methods for Neurodegeneration, " aimed at providing a roadmap for the applications of established and new molecular imaging techniques in dementia. Methods: We consider current and future implications of adopting a pathology‐based framework for the use and development of positron emission tomography techniques. Results: This approach will enhance efforts to understand the multifactorial etiology of Alzheimer's disease and other dementias. Discussion: The availability of pathology biomarkers will soon transform clinical and research practice. Crucially, a comprehensive understanding of strengths and caveats of these techniques will promote an informed use to take full advantage of these tools.